One-pot multicomponent route to propargylamines using ferric hydrogensulfate - Eshghi, Hossein; Zohuri, Gholam Hossein; Damavandi, Saman (European Journal of Chemistry, 2011)
The one-pot three-component coupling reaction of phenylacetylene, aldehyde and amine derivatives in the presence of ferric hydrogensulfate, [(Fe(HSO4)3], as an efficient heterogeneous catalyst is reported. The catalyst displayed high activity and afforded the corresponding propargylamines in good to excellent yields. This method provides the wide range of substrate applicability. Heterogeneous nature of the catalyst made it reusable for further chemical reactions.